Chemical speciation and leaching characteristics of hazardous trace elements in coal and fly ash from coal-fired power plants. (15th November 2018) - Zhao, Shilin; Duan, Yufeng; Lu, Jincheng; Gupta, Rajender; Pudasainee, Deepak; Liu, Shuai; Liu, Meng; Lu, Jianhong
Highlights: Residual Hg, water/acid soluble and exchangeable Mn have greater fraction in the coal. Residual Hg and Cr, reducible Cd and Ba are the main forms in the fly ash. Mn in the coal can pose high or very high risk on the environment based on RAC. Concentration of Cr in leaching solution from some fly ash is high. The leaching solution from the fly ash is alkaline. Abstract: This work reports the chemical speciation and leaching characteristics of seven hazardous trace elements (HTEs, including Hg, As, Cr, Cd, Ba, Mn, and Pb) in the coal and fly ash samples collected from four coal-fired power plants in China. The physical structure and chemical composition of the fly ash were characterized by the scanning electron microscope (SEM) and the energy dispersive X-ray spectrometer (EDX). The chemical speciation of HTEs in the coal and fly ash was measured by the modified three-step sequential extraction method, proposed by the European Community Bureau of Reference (BCR). Leaching characteristics of HTEs in the fly ash were investigated by a single batch leaching test. The concentration of HTEs in solid and liquid samples was determined by the direct mercury analyzer DMA 80 (Hg in solid) and the inductively coupled plasma-mass spectrometry (ICP-MS). Results show that for the coal, concentration of Hg, As, Cr, Cd, Ba, Mn, and Pb is 0.06–0.22, 0.63–4.01, 8.91–13.09, 0.06–0.15, 108.67–229.21, 49.94–100.24 and 6.74–26.38 mg/kg, respectively. Mercury is mainly in the residual form while Cd and Ba are primarily in reducible form. Compared with other HTEs, manganese in water/acid soluble and exchangeable fraction has the large percentage. For the fly ash, the concentration of Hg, As, Cr, Cd, Ba, Mn and Pb is 0.17–1.26, 5.15–25.74, 43.25–64.61, 0.56–0.70, 777.05–970.70, 163.83–831.47 and 28.94–119.57 mg/kg, respectively. Mercury and chromium are mainly in the residual speciation. Arsenic and manganese in water/acid soluble and exchangeable form have high ratio with value of 7.27–58.60% and 6.14–62.27%, respectively. Cadmium and barium are primarily in the reducible form. Based on the risk assessment code, manganese in the coal can pose high or very high risk on the environment. Leaching concentration of Cr in some fly ash is higher than permissible limits and the pH value of leaching solution for the fly ash is alkaline. Considering huge fly ash production from coal combustion and complex landfill conditions, some suitable disposal measures to minimize the risk on the environment are needed.